2019
DOI: 10.1128/aac.00074-19
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Pharmacokinetics of Oseltamivir Carboxylate in Rats after Nebulization or Intravenous Administration of Its Prodrug, Oseltamivir Phosphate

Abstract: The aim of this study was to investigate the pharmacokinetics of oseltamivir phosphate, a prodrug, and its active moiety in plasma and lung after its nebulization and intravenous administration in rats. Only 2% of prodrug was converted into active moiety presystematically, attesting to a low advantage of oseltamivir phosphate nebulization, suggesting that oseltamivir phosphate nebulization is not a good option to obtain a high exposure of the active moiety at the infection site within lung.A recent series of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…However, only 2% of OP prodrug get converted into active form pre-systematically, confirming the low benefit of OP nebulization. Therefore, it was suggested that pulmonary administration of OP may not be a good choice to get a high concentration of its active form at the infection site of the lung [ 34 ]. Extensive clinical studies are required to explore the application of respiratory administration of OP.…”
Section: Inhaled Antiviral Agentsmentioning
confidence: 99%
“…However, only 2% of OP prodrug get converted into active form pre-systematically, confirming the low benefit of OP nebulization. Therefore, it was suggested that pulmonary administration of OP may not be a good choice to get a high concentration of its active form at the infection site of the lung [ 34 ]. Extensive clinical studies are required to explore the application of respiratory administration of OP.…”
Section: Inhaled Antiviral Agentsmentioning
confidence: 99%